Generation of Semantic Layouts for Interactive Multidimensional Data Visualization - Gomez-Nieto, Erick; Nonato, Luis Gustavo (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2018: Anais do XXXI Concurso de Teses e Dissertações, 2018)
Visualization methods make use of interactive graphical representations embedded on a display area in order to enable data exploration and analysis. These typically rely on geometric primitives for representing data or building more sophisticated representations to assist the visual analysis process. One of the most challenging tasks in this context is to determinate an optimal layout of these primitives which turns out to be effective and informative. However, most techniques are able to tackle just a few fundamental requirements simultaneously, impairing their use and flexibility. In this dissertation, we propose a set of approaches for building layouts from geometric primitives that concurrently addresses a wider range of requirements. A comprehensive set of quantitative comparisons against existing methods for layout generation and applications on multimedia data visualization prove the effectiveness of our approaches.